Amendments to Part 200 of the Regulations of the Commissioner of Education, Adopted by the Board of Regents between February 27, 1987 and March 1, 1989 - New York State Education Dept., Albany; New York State Education Dept., Albany ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
Presented are the amendments to Part 200 of the regulations of New York's Commissioner of Education, adopted by the Board of Regents between February 27, 1987 and March 1, 1989. The amendments deal with: (1) the provision of consultant teacher services; (2) participation in Individualized Education Program planning conferences; (3) special education space requirements plans, and the roles of the boards of cooperative educational services and the commissioner in developing and approving the plans; (4) notification to parents and students of the end of entitlement to receive tuition-free educational services; (5) procedures for obtaining adult services; (6) due process hearings; (7) appointment of blind, deaf, and severely physically handicapped pupils to state-operated and state-supported schools; (8) notice of closing of approved private schools; and (9) state assistance for transportation of pupils with handicapping conditions. (JDD)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adults; Disabilities; Educational Policy; Educational Practices; Elementary Secondary Education; State Legislation; State Standards; New York; Legal/Legislative/Regulatory Materials